Structural analyses (Spectroscopic and in silico), DNA-binding and in vitro studies of two popular Sage Species (Salvia officinalis and Salvia fruticosa) - Bicak, Bilge; Gok, Bahar; Kecel-Gunduz, Serda; Budama-Kilinc, Yasemin; Kocyigit, Mine; Inan, Hatice Akbal; Kartal, Murat (TAYLOR & FRANCIS LTD, 2025)
The genus Salvia has high biological activity, and it is known that extracts and essential oils of Salvia species have various properties such as anti-inflammatory, antitumor, antidiabetic and antioxidant. In this study, the molecular structures, DNA binding and anticancer properties of S. fruticosa and S. officinalis species were investigated via spectroscopic, in silico and in vitro methods. According to the results of gas chromatography-mass spectrometry (GC-MS), beta-thujone, caryophyllene and beta-pinene, 1,8-cineol, endo-borneol and viridiflorol were determined to be the prominent major compounds. The DNA binding study evaluated the possible binding mode of essential oils with ctDNA as groove binding and intercalative. In vitro cytotoxicity assays were performed with C6 and SHSY-5Y cell lines, and the results showed that the essential oils had concentration-dependent cytotoxic activity. Molecular docking studies of the major compounds of essential oils and the receptors preferred as targets (B-DNA dodecamer, AChE, GSK-3 beta, Topoisomerase-I-II, Telomerase reverse transcriptase) were carried out, and it was observed that the binding profiles and binding energies of caryophyllene and viridiflorol were more prominent than the others. Molecular dynamics studies of the complex structures with the best binding energy according to molecular docking studies were carried out for 50 ns.
Keywords: Sage; Essential oil; DNA binding; Anticancer; Spectroscopy; ANTICANCER ACTIVITY; CHEMICAL-COMPOSITION; ANTIOXIDANT; ACETYLCHOLINESTERASE; DYNAMICS; IDENTIFICATION; TELOMERASE; EXPRESSION; LAMIACEAE; Plant Sciences